Silicon Quantum Dots: Synthesis, Encapsulation, and Application in Light-Emitting Diodes - Morozova, Sofia; Alikina, Mariya; Vinogradov, Aleksandr; Pagliaro, Mario (Frontiers in Chemistry, 2020)
Silicon quantum dots (SiQDs), are semiconductor Si nanoparticles ranging from 1 to 10 nm, hold great applicative potential as optoelectronic devices and fluorescent bio-marking agents due to their ability to fluoresce blue red light. Their biocompatibility, compared to conventional toxic Group II-VI and III-V metal-based quantum dots, makes their practical utilization even more attractive to prevent environmental pollution and harm to living organisms. This work focuses on their possible use for light-emitting diode (LED) manufacturing. Summarizing the main achievements over the past few years concerning different Si quantum dot synthetic methods, LED formation, characteristics and strategies for their stabilization by microencapsulation and modification of their surface by specific ligands, this work aims to provide guidance en route to development of the first stable Si-based light-emitting diodes.